CIGARETTE SMOKE INCREASES RISK FOR COLORECTAL NEOPLASIA IN INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Van Der Sloot, Kimberley; Tiems, Johan; Visschedijk, Marijn; Festen, Eleonora; van Dullemen, Hendrik; Weersma, Rinse; Kats-Ugurlu, Gursah; Dijkstra, Gerard
Abstract: Objective: Patients with inflammatory bowel disease are at increased risk of colorectal neoplasia (CRN) due to mucosal inflammation. As current surveillance guidelines form a burden on patients and healthcare costs, stratification of high-risk patients is crucial. Cigarette smoke reduces inflammation in ulcerative colitis (UC) but not Crohn's disease (CD) and forms a known risk factor for CRN in the general population. Due to this divergent association, the effect of smoking on CRN in IBD is unclear and subject of this study. Design: In this retrospective cohort study, 1, 386 IBD patients with previous biopsies analyzed and reported in the PALGA register, were screened for development of CRN. Clinical factors and cigarette smoke were evaluated. Patients were stratified for guideline-based risk of CRN. Cox-regression modeling was used to estimate the effect of cigarette smoke and its additive effect within the current risk stratification for prediction of CRN. Results: 151 (11.0%) patients developed CRN. Previously described risk factors, i.e. first-degree family member with CRN in CD (p-value=0.001), presence of post-inflammatory polyps in UC (p-value=0.004), were replicated. Former smoking increased risk of CRN in UC (HR1.72;1.04–2.84), whereas passive smoke exposure yielded no effect. For CD, active smoking (2.52; 1.14–5.58) and passive smoke exposure (1.88;1.10–3.21) significantly increased CRN risk. Addition of cigarette smoking to the current risk-stratification model significantly improved model fit for CD. Conclusion: This study is the first to describe the important role of cigarette smoke in CRN development in IBD patients. Adding this risk factor improves the current risk stratification for CRN surveillance strategies.